The Effectiveness of Tax Collection in the Republic of Poland and Polish Criminal Law on Taxation - Czichy, Krzysztof (Zeszyty Prawnicze, 2016)
One of the duties of Polish citizens listed in Art. 84 of the Polish Constitution is the liability to pay statutorily defined taxes. The procedures for the carrying out of this duty are part of Polish administrative law, but they also come under criminal law, in which the principle governing penalisation is based on the pragmatic rule of prioritising collection over and above punishment. The Polish Criminal Code on taxation prescribes a series of institutions which give the tax offender the opportunity to reduce his liability, or even exempt him altogether from criminal liability, providing he remits his dues outstanding under public law. It is self-evident that criminal law should not be treated as a substitute for administrative enforcement. However, if we are to consider the question whether the extenuation of penalties for tax evasion should depend on the offender’s satisfaction of his outstanding fiscal liabilities, and what form such an institution should take, we must first ask how effective the Polish administrative procedures for tax collection are.